PREFERENSI KONSUMEN TERHADAP SAYURAN ORGANIK DI SUPER INDO SULTAN AGUNG YOGYAKARTA - Nisa Murty Andari (FP AGRI 16 UMY 031, 2016)
CONSUMER PREFERENCE TOWARDS ORGANIC VEGETABLES AT SUPER INDO SULTAN AGUNG YOGYAKARTA. The aims of this research is to find out how the organic vegetables’ consumer characteristics, consumers decision process on purchasing organic vegetable and their preference towards organic vegetables are. This is an quantitative research which use descriptive method. There are two brands and six atributes that being evaluated in this research. The brands are TOM and TOS, while the attributes are price, packaging, brand, freshness, variant of vegetables, and organic label. The data analysis techniques used in this research are descriptive and ideal point attitude model. The result of the research, which is taken from 44 respondents, shows that freshness is the most important attribute in organic vegetables. Mostly of the consumers are married women with monthly family income more than Rp4.000.000,-. Consumers’ are motivated to consume organic vegetable because of its better nutrient compared to non-organic. Magazine and newspaper are the source of information about organic vegetables that being accesed by mostly consumers. People feel good benefits to their health after consuming organic vegetables so they decided to continue consuming organic vegetables. Overall, TOM brand gained higher score than TOS brand, and consumer prefer to buy TOM’s organic vegetables.